2021
DOI: 10.3389/fmicb.2021.632008
|View full text |Cite
|
Sign up to set email alerts
|

Peptides Derived From the α-Core and γ-Core Regions of a Putative Silybum marianum Flower Defensin Show Antifungal Activity Against Fusarium graminearum

Abstract: Fusarium graminearum is the etiological agent of Fusarium head blight (FHB), a disease that produces a significant decrease in wheat crop yield and it is further aggravated by the presence of mycotoxins in the affected grains that may cause health problems to humans and animals. Plant defensins and defensin-like proteins are antimicrobial peptides (AMPs); they are small basic, cysteine-rich peptides (CRPs) ubiquitously expressed in the plant kingdom and mostly involved in host defence. They present a highly va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 66 publications
(38 reference statements)
2
15
0
Order By: Relevance
“…Of Fusarium species, F. culmorum appeared to be the most sensitive species. The antimicrobial properties of γ-cores of defensins were reported earlier in a number of studies [16,[33][34][35][36][37][38][39][40][41][42][43][44]. However, in our study, for the first time, a broad panel of plant and human pathogens, including fungi and bacteria, was simultaneously assayed and shown to be sensitive to the DEFL-derived γ-core-containing peptides.…”
Section: Discussionsupporting
confidence: 70%
“…Of Fusarium species, F. culmorum appeared to be the most sensitive species. The antimicrobial properties of γ-cores of defensins were reported earlier in a number of studies [16,[33][34][35][36][37][38][39][40][41][42][43][44]. However, in our study, for the first time, a broad panel of plant and human pathogens, including fungi and bacteria, was simultaneously assayed and shown to be sensitive to the DEFL-derived γ-core-containing peptides.…”
Section: Discussionsupporting
confidence: 70%
“…and its underlying mechanism has been studied by Yun and Lee [ 18 , 61 ] and Janeczko and Kochanowicz [ 62 ]. Fernández, et al [ 63 ] found significant inhibition against Fusarium graminearum Schwabe for four flower defensins from milk thistle. Safarpoor, et al [ 64 ] reported moderate antifungal activities of ethanolic extracts of milk thistle against C. albicans and Aspergillus oryzae (Ahlb.)…”
Section: Discussionmentioning
confidence: 99%
“…However, their exact biological role in the immune response remained unknown. Structure–function studies of the classical defensins showed that the antimicrobial activity is associated, at least in part, with their γ-core motifs [ 17 , 30 ]. In our studies of tomato CRPs, we showed that the γ-core motifs of the CRPs belonging to other peptide families, such as snakins, MEG (Maternally Expressed Gene) peptides, and nsLTPs, also possess antimicrobial activity [ 18 ].…”
Section: Discussionmentioning
confidence: 99%